Importance and Challenges of SMEs: A Case of Pakistani SMEs - Muhamamd Zulqarnain Arshad; Waris Ali Khan; Muhammad Ali Arshad; Majid Ali; Athifah Najwani Shahidan; Wan Zhalkiatul Aida Ishak (2020)
This paper attempt to highlight the importance and challenges that SMEs facing now a days. The small and medium-sized enterprises (SMEs) regarded as a key contributor in progression of an economy and main pillar of GDP of any country. SMEs are the major source in generating employment. Generally, the large firms are often thought as the larger contributors towards the economic development and foreign exchange earnings but now this point of view has been changed because countries like Korea, Taiwan, and Japan have developed and boosted their economies through the Small and Medium Enterprises businesses.